Interview with Stella Wisdom, Digital Curator at the British Library - Wisdom, Stella (Gamevironments, 2021)
This interview with Stella Wisdom, Digital Curator at the British Library in the UK, focuses on illustrating the ways video game technologies have become inspirational for curatorial practice and public outreach activities that support new research on digital media. Wisdom discusses her role working with games and related games media and activities from the perspective of a cultural heritage organization working with the preservation and collection of complex digital artifacts. She identifies games as a significant kind of emerging format in which a traditional heritage organization, like the British Library, has become increasingly interested based on the complex cultures, stories and media that intersect with games and users. She shares her experience running games competitions and hosting activities for developers and players, including with children, demonstrating how games have become a key focal point for libraries, museums, and digital archiving practices helping to create new knowledge. Her close cooperation with video game developers (such as Inkle and Crytek) and with other creative industry partners illustrates the importance of understanding games as complex material and game social objects. The transhistorical connections among games and with other media forms, analog and digital, in the Library's collections, provide inspiration for many interesting collaborative research projects. This work forms a foundation for others interested in researching, developing and preserving games as meaningful cultural artifacts for analysis.